X(x+5)-(x-2)(x+3)=3(x+1)-11
Răspunsuri la întrebare
Răspuns de
2
x^2+5x - ( x^2 - 2x + 3x - 6 ) = 3x + 3 -11
x^2 + 5x - x^2 +2x - 3x + 6 = 3x + 3 - 11
4x+6 = 3x - 8 | - 3x
x + 6= -8 | -6
x= - 14
x^2 + 5x - x^2 +2x - 3x + 6 = 3x + 3 - 11
4x+6 = 3x - 8 | - 3x
x + 6= -8 | -6
x= - 14
Răspuns de
3
----------------------------
Anexe:
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă